Biodegradation of polypropylene by filter-feeding marine scallop Mizuhopecten yessoensis: infrared spectroscopy evidence - Chelomin, Viktor Pavlovich; Istomina, Aleksandra Anatolyevna; Mazur, Andrey Alexandrovich; Zhukovskaya, Avianna Fayazovna (Frontiers in Marine Science, 2024)
The problem of environmental pollution by plastics is global in nature and needs to be addressed as soon as possible. Realization of the importance of this problem contributed to the study of degradation and biodegradation of synthetic polymers. It turned out that the driving force of plastic fragmentation along with abiotic factors can be biotic. Based on the above, we investigated the in vitro biodegradation of polypropylene (PP) fragments in digestive gland homogenates and crystalline styles of the bivalve mollusk Mizuhopecten yessoensis. Fourier transform infrared spectroscopy showed changes in the chemical composition of functional groups on the plastic surface. Enzyme complexes of crystalline styles enhanced the biodegradation of PP fragments to a larger extent than did digestive glands. The results obtained using M. yessoensis as an example suggest that marine phytophagous filter-feeding invertebrates may accelerate the biodegradation of synthetic polymers. The study provides a basis for rethinking the nature of relationships between marine invertebrates and microplastic polluting the marine environment.